Improving Student Initial Reading and Reading Comprehension Skills Using Picture Card Media at 7th Grade SMP Bina Insan Mandiri Bogor - Yose Eduar Muda (Pekobis : Jurnal Pendidikan, Ekonomi, dan Bisnis, 2024)
Improving Student Reading Loud and Reading Comprehension Skills Using Picture Card Media at SMP Bina Insan Mandiri Bogor. The aim of this study was to improve beginning reading skills using picture cards for 7th-grade students at SMP Bina Insan Mandiri Bogor. This type of research is Classroom Action Research (PTK) which is conducted in two cycles. The research design uses the Kemmis Mc model. Teggart with the subjects in this study were grade 7th with a total of 35 students. Techniques for collecting data used 1) oral reading tests and written reading comprehension tests, 2) observation, and 3) documentation. The data analysis technique uses descriptive statistical analysis, namely by finding the average. Indicators of student success must be achieved with a class average of 70 and a completeness of 80%. The results of the study show that learning about early reading using picture cards in English subjects can improve the reading skills of grade 7th at SMP Bina Insan Mandiri Bogor. 2. Pre-cycle reading ability was 65 and 54% completeness, in cycle 1 there was an increase to 68 and 66% completeness, in cycle II 74.14 with 88% completeness. In this study, the reading ability of class 7th SMP Bina Insan Mandiri Bogor with pronunciation, intonation, and reading comprehension increased until they reached the minimum mastery criteria (KKM) that had been set, namely 70 and 80% completeness in class. In cycle 1 use picture cards with a size of 13x6cm and with attractive colours. In cycle II use a bigger card, size 18x6 to facilitate learning for students in understanding reading.